THE MASSES OF THE IONIZED GAS OF PLANETARY NEBULAE ENVELOPES IN LARGE MAGELLANIC CLOUD - Holovatyy, V.; Demchyna, A. (Одеські астрономічні публікації, 2013)
The masses of ionized gas in the shells of planetary nebulae which belong in the Large Magellanic Cloud are calculated by three different ways. The value of mass is calculated for the cases: 1) spherical, 2) elliptical forms of envelopes and 3) commonly known method based on the line ratio F(Hβ) of the shell to its emissivity of ε(Hβ). It is shown that the values of masses Mi of nebulae envelopes differ up to 50%. The values of Mi calculated by the other methods which differ more from previous ones. We consider the dependence of Mi on the radius and the electron density in the envelopes of nebulae.